Visceral obesity and anastomotic leakage rates in colorectal cancer: a systematic review and meta-analysis - Yu, Linchong; Wu, Wenjiang; Xia, Shijun; Li, Yue; Xu, Zhigang (Frontiers in Oncology, 2023)
Background: Numberous studies have heatedly discussed whether obesity is a risk factor for anastomotic leakage (AL) because of the increasing number of colorectal cancer (CRC) cases and high incidence of CRC in patients with obesity. Objective: We aimed to explore the relationship between visceral obesity(VO) and AL after CRC surgery. The databases of Pubmed, Embase, and the Cochrane Library were searched for relevant data and articles published until November 1, 2022. We identified the difference in the incidence of AL after CRC surgery between patients with and without VO. The quality of included studies was evaluated using the Newcastle-Ottawa Scale, and odds ratio (OR) and 95% CI were used to assess the association between VO and AL. Results: This meta-analysis included 7 studies with 2,136 patients. The OR of patients with VO versus those without VO was 2.15 (95%CIs = 1.46-3.15, test for heterogeneity: P = 0.29, I 2 = 18%) based on the fixed-effect model in seven studies. Notably, the difference between the two groups was statistically significant (Z = 3.91 P < 0.0001). Patients with VO in the colon cancer group exhibited a higher incidence of AL (OR = 2.88, 95% CIs = 1.38-5.99, test for heterogeneity: P = 0.27, I 2 = 20%) than those in the rectal cancer group (OR = 2.74, 95% CIs = 1.13-6.65, test for heterogeneity: P = 0.20, I 2 = 38%). In the studies in the relevant literature, heterogeneity was low. Regarding patients with VO, four Asian studies reported increased morbidity due to AL (OR = 2.79, 95% CIs = 1.35-5.78, test for heterogeneity: P = 0.35, I 2 = 9%) compared with three non-Asian studies.Conclusions: Our findings confirmed the significant relationship between VO and AL. Thus, VO could be considered a reliable risk factor of surgery for colon cancer.